2011
DOI: 10.1186/1471-2164-12-489
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of naked DNA influence nucleosome positioning and correlate with transcription start and termination sites in yeast

Abstract: BackgroundIn eukaryotic organisms, DNA is packaged into chromatin structure, where most of DNA is wrapped into nucleosomes. DNA compaction and nucleosome positioning have clear functional implications, since they modulate the accessibility of genomic regions to regulatory proteins. Despite the intensive research effort focused in this area, the rules defining nucleosome positioning and the location of DNA regulatory regions still remain elusive.ResultsNaked (histone-free) and nucleosomal DNA from yeast were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 64 publications
4
49
1
Order By: Relevance
“…1) prompted us to test the role of DNA sequence. Some studies suggest that DNA sequence is a major factor in nucleosome positioning (64,65), while others argue that it may be only a partial factor (66)(67)(68)(69). To test the role of sequence in vitro, we used a Förster resonance energy transfer (FRET) competition assay (44) to compare H2A-H2B affinities for the six different GAL promoter (PRO) and open reading frame (ORF) sequences, all of ϳ150 bp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) prompted us to test the role of DNA sequence. Some studies suggest that DNA sequence is a major factor in nucleosome positioning (64,65), while others argue that it may be only a partial factor (66)(67)(68)(69). To test the role of sequence in vitro, we used a Förster resonance energy transfer (FRET) competition assay (44) to compare H2A-H2B affinities for the six different GAL promoter (PRO) and open reading frame (ORF) sequences, all of ϳ150 bp.…”
Section: Resultsmentioning
confidence: 99%
“…5B). Since DNA sequence can directly affect nucleosome stability and contribute to in vivo nucleosome dynamics (64,65), we tested the fragments for their intrinsic ability to form nucleosomes. Using the 601 positioning sequence (59) as a control, the GAL fragments were analyzed for the formation of stable, positioned nucleosomes by salt reconstitution with native histones (49) (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, recent genome-wide nucleosome mapping analyses from our group have revealed that housekeeping genes display unique nucleosome architectures, with large nucleosome refractory regions upstream the TSS (unpublished data). In general then, the interplay between DNA physical properties and regulatory regions could be rationalized in terms of nucleosome positioning (16), favoring the presence of sequences with unique deformation properties in promoter regions, although this might not be the only underlying mechanism, and this would probably vary from gene to gene.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, core promoters and associated TSSs are DNA segments with an intrinsic ability to act as regulatory regions, as they are depleted in nucleosomes and need to bind to a large number of regulatory proteins, which certainly require special physical properties of the DNA fiber. According to this paradigm, we consider that promoters can be defined as regions of unusual physical deformability (13,15,16), which (even in the absence of traditional sequence motifs) might favor either a suitable nucleosome positioning pattern for protein recognition (17) or an effective binding of core promoter-binding proteins and RNA polymerase (12,18). Notwithstanding, genome-wide analysis of the DNA physical properties (13) revealed that ‘promoter-like’ physical signals appear in regions without evidence for real promoters, challenging the existence of a regulatory physical code in DNA, or alternatively, suggesting the presence of many hidden promoter regions in the human genome.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning other physical models proposed using either different di-or tri-nucleotide coding tables (Miele et al 2008) rather than the PNuc coding table used here or constructed ab initio (Tolstorukov et al 2007;Morozov et al 2009;Tolkunov and Morozov 2010), the obtained performances are even poorer, e.g. sequence-dependent elasticity provides a very good match at TSS and TTS of yeast genes (Deniz et al 2011).…”
Section: Modelling Of In Vitro Nucleosome Occupancy Data In S Cerevimentioning
confidence: 92%